Analysis Atmosphere Management of Price Reduction and Product Quality on Consumer Buying Interest in the Covid-19 Pandemic - Feby Milanie (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This research was conducted to look for the effect of store atmosphere, price discounts, and product quality on consumers buying the interest of RA Jeans at PT. Matahari Department Store Plaza Medan fair. The population in this research was unknown, so the number of samples was determined using the Zikmund formula the number of samples was 97 respondents. This research used an associative approach with quantitative data that was processed with SPSS application version 24.0. The Source of data used primary data taken directly from respondents. The analytical method used was multiple linear regression. The research was conducted from July to December 2019. The results showed that store atmosphere, price cuts, and product quality had a positive and significant effect both partially and simultaneously on consumer buying interest, where the discounted variable was the most dominant variable influencing consumer buying interest. Store atmosphere, price discounts and product quality contributed 86.6% in the formation of consumer buying interest. Store atmosphere, price discounts, and product quality also had a very strong relationship to consumer buying interest.